Optimasi Konsentrasi Pupuk Daun Untuk Pertumbuhan dan Pengendalian Penyakit Curvularia Pada Bibit Kelapa Sawit - Muhammad Wildan Azzamuddin; Edi Wiraguna (Asosiasi Riset Ilmu Tanaman Dan Hewani Indonesia, 2025)
Fungal infections, such as those caused by Curvularia, can interfere with the vegetative growth and reduce the quality of oil palm seedlings, particularly in the main nursery phase. One solution to improve resistance to pathogens and support vegetative growth is by applying the right foliar fertilizer. This study aimed to determine the effect of Kenfolan foliar fertilizer application on vegetative growth and the level of Curvularia infection in oil palm seedlings during the main nursery phase. The study used a Completely Randomized Design (CRD) with five treatments of Kenfolan fertilizer concentrations: 0 ml/L (P1), 1 ml/L (P2), 2 ml/L (P3), 3 ml/L (P4), and 4 ml/L (P5), each repeated three times. The parameters measured included seedling height, stem diameter, number of fronds, and the percentage of Curvularia infection. Data analysis was performed using ANOVA followed by Duncan’s Multiple Range Test (DMRT) at a 5% significance level. The results showed that treatment P4 (3 ml/L) provided the best vegetative growth, with seedling height reaching 40.07 cm, stem diameter of 1.58 cm, and an average of 4.25 fronds. Additionally, treatments P3 (2 ml/L) and P4 (3 ml/L) successfully suppressed Curvularia infection, with no infection found in these treatments. In contrast, treatment P1 (control) showed the highest infection level of 33%, while P5 (4 ml/L) increased the infection compared to P3 and P4. Based on the results, the application of Kenfolan foliar fertilizer at a dose of 3 ml/L (P4) was the most effective in improving vegetative growth and suppressing Curvularia infection in oil palm seedlings in the main nursery phase.